A conserved non-reproductive GnRH system in chordates. - Takehiro G Kusakabe; Tsubasa Sakai; Masato Aoyama; Yuka Kitajima; Yuki Miyamoto; Toru Takigawa; Yutaka Daido; Kentaro Fujiwara; Yasuko Terashima; Yoko Sugiuchi; Giorgio Matassi; Hitoshi Yagisawa; et al. (PLoS ONE, 2012)
Gonadotropin-releasing hormone (GnRH) is a neuroendocrine peptide that plays a central role in the vertebrate hypothalamo-pituitary axis. The roles of GnRH in the control of vertebrate reproductive functions have been established, while its non-reproductive function has been suggested but less well understood. Here we show that the tunicate Ciona intestinalis has in its non-reproductive larval stage a prominent GnRH system spanning the entire length of the nervous system. Tunicate GnRH receptors are phylogenetically closest to vertebrate GnRH receptors, yet functional analysis of the receptors revealed that these simple chordates have evolved a unique GnRH system with multiple ligands and receptor heterodimerization enabling complex regulation. One of the gnrh genes is conspicuously expressed in the motor ganglion and nerve cord, which are homologous structures to the hindbrain and spinal cord of vertebrates. Correspondingly, GnRH receptor genes were found to be expressed in the tail muscle and notochord of embryos, both of which are phylotypic axial structures along the nerve cord. Our findings suggest a novel non-reproductive role of GnRH in tunicates. Furthermore, we present evidence that GnRH-producing cells are present in the hindbrain and spinal cord of the medaka, Oryzias latipes, thereby suggesting the deep evolutionary origin of a non-reproductive GnRH system in chordates.